2021
DOI: 10.1016/j.molcel.2021.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative binding between distant transcription factors is a hallmark of active enhancers

Abstract: Enhancers harbor binding motifs that recruit transcription factors (TFs) for gene activation.While cooperative binding of TFs at enhancers is known to be critical for transcriptional activation of a handful of developmental enhancers, the extent TF cooperativity genome-wide is unknown. Here, we couple high-resolution nuclease footprinting with single-molecule methylation profiling to characterize TF cooperativity at active enhancers in the Drosophila genome. Enrichment of short MNase-protected DNA segments ind… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 64 publications
(70 reference statements)
3
39
0
Order By: Relevance
“…Notably, at dimeric motif sites, TFs tended to bind initially as monomers with subsequent dimerisation presumably stabilising the DNA–protein complex [ 119 ]. Interestingly, at non-dimeric sites, physical interactions between co-bound TFs were not necessary [ 119 ], consistent with evidence from Drosophila where co-occupied DNA-bound TFs were often spaced quite widely apart (> 50 bp) [ 118 ]. Jointly, these results point to synergistic mechanisms between different TFs that do not require direct protein–protein interaction.…”
Section: Organisation and Function Of Enhancers In Cissupporting
confidence: 61%
See 2 more Smart Citations
“…Notably, at dimeric motif sites, TFs tended to bind initially as monomers with subsequent dimerisation presumably stabilising the DNA–protein complex [ 119 ]. Interestingly, at non-dimeric sites, physical interactions between co-bound TFs were not necessary [ 119 ], consistent with evidence from Drosophila where co-occupied DNA-bound TFs were often spaced quite widely apart (> 50 bp) [ 118 ]. Jointly, these results point to synergistic mechanisms between different TFs that do not require direct protein–protein interaction.…”
Section: Organisation and Function Of Enhancers In Cissupporting
confidence: 61%
“…While it is clear that enhancers typically favour the more flexible models of sequence organisation, the degree of necessary cooperation between TFs is less obvious, particularly since TF binding to DNA appears to be very transient [ 113 117 ]. Recent technological advances such as single molecule footprinting (SMF) have begun to unpick how TFs work with each other at enhancers [ 118 , 119 ]. First developed in Drosophila , SMF can detect the binding of multiple TFs on a single DNA molecule [ 116 ].…”
Section: Organisation and Function Of Enhancers In Cismentioning
confidence: 99%
See 1 more Smart Citation
“…The discovery that TFs work in tandem to regulate the expression of their targets ( 13 ) has sparked the development of a variety of computational methods for predicting cooperativity among TFs and other regulatory proteins by looking at regulatory element co-occurrences ( 14–20 ). In fact, a recent report has demonstrated that TF cooperativity in active enhancers is dominant ( 21 ). Despite the demonstrated ability of deep neural networks to extract regulatory signals directly from sequence, there are very few studies that explore cooperativity between regulatory features in genomic data using these methods.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the variable activity of enhancers across developmental states adds an additional layer of complexity as an element involved robust transcriptional activity for a particular tissue type or stimulus response might have no detectable TF occupancy in cells where the enhancer is not yet active (Li et al, 2008;Thurman et al, 2012). Similar to PWM searches, confidence in candidate enhancers ascertained through ChIP-Seq can be improved by studying multiple TFs in search of the density of TFBSs that correlate with the cooperative interactions that underlie enhancer function (Spitz and Furlong, 2012;Rao et al, 2021). However, the practicality of such an approach is tempered by the cost-benefit analysis of studying multiple TFs whose interactions represent a tiny fraction of a highly heterogeneous population of regulatory elements.…”
Section: High-throughput Prediction Of Enhancer Elements Using Bioinformaticsmentioning
confidence: 99%